Percutaneous Treatment of Concomitant Severe Aortic Stenosis and Thoracoabdominal Aortic Aneurysm. (February 2022) - Painchaud-Bouchard, Ariane-Sophie; Potvin, Jeannot; Forcillo, Jessica; Ruz, Ricardo; Elkouri, Stephane
Purpose: Although rare in occurrence, symptomatic severe aortic stenosis and large thoracoabdominal aortic aneurysm (TAAA) found in combination pose a real therapeutic challenge, especially in elderly frail patients. Surgical approaches for combined treatment are complex and at high risk of complications while staged procedures carry the risk of an unfavorable evolution of the condition temporarily left untreated. Minimally invasive approaches may therefore prove a more suitable strategy for these patients. Case Report: We present the case of a 78-year-old woman with symptomatic severe aortic stenosis (AS) and a TAAA of 7.8 cm in diameter. Transcatheter treatment of both conditions was successfully performed in a staged manner. The first intervention consisted of combined transfemoral transcatheter aortic valve implantation (TAVI) immediately followed by a zone 3 thoracic endovascular aortic endoprosthesis deployment. In order to reduce the extent of intercostal arteries coverage and mitigate the risk of medullar ischemia, a second-stage percutaneous endovascular treatment of the TAAA was performed with a customized 4-fenestration prosthesis. Early and 12-month clinical and radiologic follow-up were favorable. Conclusion: This case demonstrates how a strong multidisciplinary collaboration allows for successful resolution of complex clinical scenarios.